Nutrient adequacy of elderly in Guna Budi Bakti Nursing Home: a pilot study in Medan City-Indonesia - Evawany Aritonang,; Jumirah,; Gustin Dytha Sari, (Penerbit UKM, 2010)
Health condition in the elderly is determined by the quality and quantity of food and nutrient being consumed. However, the nutrient adequacy among elderly people at nursing home in Indonesia has rarely been investigated. Therefore, a cross sectional study was conducted to determine nutrient adequacy in Guna Budi Bakti nursing home in the city of Medan. Elderly food intake was assessed by three days food weighing method and compared to the Indonesian Recommended Dietary Allowances (RDA). Energy intake reached >100% of RDA. Although the majority of subject able to meet 70% of RDA for protein and vitamin A, a proportion of subject could not meet the recommendation of protein (26.6%) and vitamin A (28.3%). Calcium and ferum intake were approximately 20% of RDA Furthermore, there is a need for a balanced food to planned and provided at the nursing home in the study